2016
DOI: 10.1002/jctb.5022
|View full text |Cite
|
Sign up to set email alerts
|

Distinctly different bubble behaviors in a bubble column with pure liquids and alcohol solutions

Abstract: BACKGROUND: Bubble column reactors are widely used in chemical processes and wastewater processing. The relevant properties of surface tension play important roles in the hydrodynamics and bubble coalescence and breakup. However, the underlying mechanisms are complicated and need further research. In this work, the bubble behaviors were studied in a bubble column of 0.1 m i.d. with pure liquids of different surface tension and alcohol solutions varying in concentration and alcohol type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Similar results were presented by Syeda et al [165] and by Shah et al [161]. These studies [161,[164][165][166] explain the trend of ε G with respect to the mole fraction of one of the two components in the liquid mixture, based on the model proposed by Andrew [167].…”
Section: R4supporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were presented by Syeda et al [165] and by Shah et al [161]. These studies [161,[164][165][166] explain the trend of ε G with respect to the mole fraction of one of the two components in the liquid mixture, based on the model proposed by Andrew [167].…”
Section: R4supporting
confidence: 78%
“…Pjoteng et al [125] (d c = 0.10 m, H C = 1.8 m) reported an increase in ε G with the addition of ethanol (0.5% wt ), up to a pressure of 9 MPa. Guo et al [164] studied a small diameter (d c = 0.1 m) and small-scale (H c = 1.8 m) bubble column. They found that ε G first increases, and then decreases, with an increasing ethanol concentration, owing to the non-linear effect of the alcoholic solution on the "coalescence-induced" and "non-coalescence-induced" bubbles.…”
Section: R4mentioning
confidence: 99%
“…Guo et al (2016) studied a small-diameter (d c =0.1 m) and small-scale (H c =1.8 m) bubble column by using nitrogen as the gas phase and various solutions of ethanol and nbutanol as the liquid phase. They found that the gas holdup first increases rapidly, and then decreases slowly when further increasing the ethanol concentration.…”
Section: Comparison With the Dual Effect Observed In Binary Systems Wmentioning
confidence: 99%
“…A similar result was presented by Shah et al (1985), who investigated the entire range of concentrations for the ethanol-water system. All these studies (Bhaga et al, 1971;Guo et al, 2016;Shah et al, 1985;Syeda et al, 2002) explained the trend of the gas holdup with respect to the mole fraction of one of the two components in the liquid mixture on the basis of the dynamic surface tension model by Andrew (1960).…”
Section: Comparison With the Dual Effect Observed In Binary Systems Wmentioning
confidence: 99%
“…S8). The bubble inrush phenomenon observed from the micrometer orifice (Figs and ) induces a significant fluctuation near the bubble interface and then directly affects the formation of the following bubbles, leading to the enhancement of the volumetric mass transfer coefficient K L a . Obviously, the increase of K L a becomes more remarkable when bubbling via the orifice with smaller diameter, which indicates that the orifice gas velocity makes an apparent positive impact on K L a , especially for bubbling from the orifice with smaller diameter.…”
Section: Resultsmentioning
confidence: 99%